Vortex dynamics in phase separated Tl0.58Rb0.42Fe1.72Se2 crystals - Haberkorn, Nestor Fabian (2016)
We report the critical current density Jc and the vortex dynamics in phase-separated Tl0.58Rb0.42Fe1.72Se2 crystals by performing magnetization measurements. Structural investigation reveals micro- and nanoscopic phase separation between 122 (superconducting) and 245 (not superconducting) phases. Micrometric phase separation refers to 245 islands with typical diameters of 2 µm embedded in a multiply-connected 122 superconducting network. Nanoscopic phase separation refers to 245 nanoprecipitates embedded in the 122 superconducting paths. The 245 nanoprecipitates with size comparable to the coherence length produce strong vortex pinning. It was observed that the temperature dependence of the flux creep rate presents a peak at intermediate temperatures and magnetic fields lower than 0.5 T. The peak is systematically suppressed as the magnetic field is increased, and it could be related with relaxation generated by double-kink excitations. Double-kinks are low-energy depinning excitations usually associated with strong pinning produced by correlated disorder.